Being philosophical an introduction to philosophy and its methods - Hetherington, Stephen (Cambridge, United Kingdom Polity Press, 2024)
"Being Philosophical guides readers through the perplexing initial moments of meeting philosophy by taking them inside philosophical thinking as an activity. In a beginner-friendly voice, Stephen Hetherington elucidates how intellectual 'tools' from a diversity of traditions, East and West, can enable us to start doing philosophy--that is, to think 'from scratch' in a philosophical way. He explores many classical topics and issues that have preoccupied philosophers from Plato, early Buddhists and Confucius to Karl Marx and beyond -- selves, souls, identity, will, knowing and reasoning, acting morally, and more -- and presents possible methods for responding to different theories. Inviting and conversational, Being Philosophical is the book needed by every new philosophy student - or anyone wondering whether they might want to explore the world of philosophy." -- Provided by publisher.
Keywords: Methodology; Philosophy